ARABIC LEGAL PHRASEOLOGY IN POSITIVE LAW AND JURISPRUDENCE: THE HISTORICAL INFLUENCE OF TRANSLATION - Sonia HALIMI (Comparative Legilinguistics, 2021)
The present study examines Arabic legal phraseology formation from the standpoint of positive law and jurisprudence. It claims that phraseological constructions in Arabic legislative and statutory texts are largely influenced by the translation process of Roman law texts. However, scholarly literature still relies to some extent on formulae used in the Islamic jurisprudence. To illustrate this, three examples of legal principles anchored in Islamic jurisprundence, known as legal maxims, are discussed along with their corresponding expressions in positive law in modern-day Arabic. Ultimately, the purpose of this paper is twofold: firstly, to demonstrate that the phraseology present in many Arabic positive laws stems from a historical translation process that started in the beginning of the 20th century; secondly to emphasize the significance of textual genre awareness in legal translation. Concretely, the introductory section provides an overview of recent studies that have addressed legal phraseologisms. It is followed by a section on the historical role of translation in the construction of certain phraseologisms. The general legal principles of (a) burden of proof, (b) presumption of innocence, and (c) the pacta sunt servanda principle are then examined in order to shed light on the influence of both the Civilist tradition and Islamic jurisprudence on the use of legal Arabic today, as well as to demonstrate how the translation of phraseologisms is dependent on the parameters of genre. The analysis leads to the conclusion that proper use of phraseologisms, whether in drafting or translation, is closely linked to knowledge of phraseology formation and the historical influence of translation.